2003
DOI: 10.1159/000076052
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Acoustic Rhinometry, Rhinoresistometry and Flow Simulation in Noses before and after Turbinate Surgery: A Model Study

Abstract: Background: Especially to young examiners, the interpretation of rhinometric findings seems to be difficult. In order to understand rhinometric assessments precisely, knowledge of airflow behavior in the nose is necessary. We therefore investigated the influence of nasal concha surgery on acoustic rhinometry and rhinoresistometry in a model. Method: Six nose models were examined with acoustic rhinometry and rhinoresistometry, each of these models with its lateral wall altered to represent various conditions af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 11 publications
0
17
0
1
Order By: Relevance
“…18 In the healthy nose, the air flows across the entire body of nasal mucosa; thus, there is vast trigeminal feedback sent from the receptors of the entire cavity. Proetz 2 and Grü tzenmacher et al 18 have shown that when, for example, an IT is removed, almost the entire airflow will converge into this enlarged empty cavity, along the nasal floor, and will not become elevated or deflected into Abbreviations: ENS, empty nose syndrome; ET, eustachian tube; improv, improvement; IT, inferior turbinate; MT, middle turbinate; PT, partial turbinectomy; SNOT-20, 20-item Sino-Nasal Outcome Test; SP, surgical procedure; TS, turbinate surgery. a ENS-type indicates patients who have lost relatively little of their turbinate tissues and whose turbinates appear to be almost normal in size; ENS-both, patients in whom both the IT and MT were at least partially resected.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In the healthy nose, the air flows across the entire body of nasal mucosa; thus, there is vast trigeminal feedback sent from the receptors of the entire cavity. Proetz 2 and Grü tzenmacher et al 18 have shown that when, for example, an IT is removed, almost the entire airflow will converge into this enlarged empty cavity, along the nasal floor, and will not become elevated or deflected into Abbreviations: ENS, empty nose syndrome; ET, eustachian tube; improv, improvement; IT, inferior turbinate; MT, middle turbinate; PT, partial turbinectomy; SNOT-20, 20-item Sino-Nasal Outcome Test; SP, surgical procedure; TS, turbinate surgery. a ENS-type indicates patients who have lost relatively little of their turbinate tissues and whose turbinates appear to be almost normal in size; ENS-both, patients in whom both the IT and MT were at least partially resected.…”
Section: Commentmentioning
confidence: 99%
“…The IT directs airflow toward the middle meatus. 3,18 The turbinates themselves are bony structures with mucosal and submucosal covering. The IT has a great deal of capacitance vessels to alter its size and thus alter airflow.…”
Section: Commentmentioning
confidence: 99%
“…Loss of turbinate tissue ultimately disrupts and destroys the meatal structure, causing turbulent, less efficient, and less sensate airflow. 15,16 The meati that are formed by turbinates, septum, and nasal floor walls are very narrow, offering a mechanism of resistance and thereby limiting the total amount of airflow, while in turbinates lacking ENS patients the nasal airflow resistance is substantially decreased. We found a lower mean NAR score (1.03) in our study cohort before operation, and the findings derived from acoustic rhinometry were similar to previous ENS studies.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that simulated inferior turbinate reduction would result in a broad reduction of pressure along the nasal airway, including the regions distant from the inferior turbinate vicinity. Grutzenmacher et al [4] created six polymer models of nasal cavity including models with turbinate resection. Unfavorable flow course and strong turbulence were observed after nasal turbinate resection.…”
Section: Introductionmentioning
confidence: 99%